Sororidade e empoderamento: uma análise do discurso feminista no Facebook - Rosa, Mariana Guidetti (Universidade Federal de São Carlos, 2019)
The feminism, as well as circulating in other spheres of communication, is a subject that has been discussed mainly on the web; it is possible to notice a growing circulation of texts about the referred movement in different websites, blogs and social networks. The feminist pages on the social network Facebook have an increasing number of followers every day. Based on the questioning about the different meanings that circulate on the web and with the aim of understanding how feminist discourse manifests itself in two feminist pages on Facebook ("Empodere Duas Mulheres" and "Não me Kahlo", each of both with approximately 1 million followers and many shares) we intend to analyze in this study a selection of feminist texts containing the words sisterhood and empowerment, culled as the corpus of the research. The choice of the Facebook medium is due to the fact that research needs to be developed to deal with the new textual modalities of the web, which emerged due to the development of new communication technologies at the end of the 20th century (Maingueneau, 2015). This Master's dissertation is theoretically and methodologically anchored in Michel Pêcheux's French Discourse Analysis and the theories of hypergenrer and scenography proposed by Dominique Maingueneau. We analyze the different meanings that circulate in the multimodal texts that have the two words (sisterhood and empowerment) of two pages of the social network Facebook: "Empodere Duas Mulheres" and "Não me Kahlo", having as an interpretative hypothesis that there are different discursive formations. In order to prove this hypothesis, we first verify how the texts selected for the analyzes from certain courses (Maingueneau, 2015) and inscription in certain discursive formations (Maingueneau, 2015) are inscribed in the hypergenrer (Maingueneau, 2015). The analysis will be based on the recognition of the different scenographies and how they are mobilized; in the sequence, how the interdiscourse breaks in the texts chosen for analysis. Finally, through unexpected courses (Maingueneau, 2015), it will be possible to make explicit the unforeseen relations and contradictions within a discursive formation, to measure the dispersion and to explore the dissemination of the senses of the chosen words. After the analysis, we intend to describe the functioning of the medium and clarify how the elements of coercion, responsible for determining and restricting the discursive functioning of the multimodal texts, allow the dissemination and construction of the present discourses.
Keywords: Discurso; Hipergênero; Cenografia; Feminismo; Discourse; Scenography; Feminism; Hypergenrer; LINGUISTICA, LETRAS E ARTES::LETRAS::LINGUA PORTUGUESA; LINGUISTICA, LETRAS E ARTES::LETRAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA